(untitled) (Bangladesh Journal of Medicine, 2021)
Objectives: To assess systolic left ventricular function determined by left ventricular ejection fraction (LVEF) with the help of Echocardiography and correlate with ECG findings in patients of AMI. Methods: One hundred (100) cases of acute myocardial infarction were studied in the Department of Cardiology, DMCH from July 2015 to December 2015. It was an observational study. All selected patients were interviewed with a preformed questionnaire and were observed up to 7 days in hospital. Echocardiography was done to assess left ventricular ejection fraction (LVEF) by applying Teichholz (cube) formula. Results: 83% of them were males and 17% of them were females. Mean age (±SD) was 52.24±11.59 years (range 34-82 years). The important risk factors among the study subjects, was hypertension (45%) (Male 40.96%; Female 64.7%) followed by Diabetes mellitus (33%) (Male 31.32%; Female 41.17%). Most of the admitted patients could reach in hospital within 4-12 hours of onset of symptoms and most of the patients of acute myocardial infarction had anterior wall involvement (37%). Mild systolic LV dysfunction (52.87%) was revealed in echocardiography among the survivors. Conclusion: The incidence of AMI was seen common among farmers who were mostly hypertensive. Systolic LV dysfunction was common in most patients where anterior wall involvement was present. Bangladesh J Medicine July 2022; 33(1) : 12-18